A Preschool Child: Between Reality, Expectations and the Need for Uninhibited Play - Kinga Kuszak (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The article analyses the contemporary neoliberal reality and educational practices used in preschool education as well as contradicting expectations held of preschool children. It starts with a general description of neoliberalism as a set of practices, a discourse and a worldview which influences all spheres of contemporary people's functioning. The author proceeds to summarize the neoliberal discourse on childhood. She presents the following images of childhood formulated within its framework: childhood as an investment, childhood inscribed within a procedure, childhood characterized by a shortage of time, virtual childhood, and commercial childhood. These discourses and the consequent practices clash with expectations held of children. The article points out the following expectations to which children are held: ability to manage their own time, agency and independence, focus and attentiveness, ability to select offers and make a choice. The author attempts to view children's play as a form of investment into good quality childhood. She points out selected elements of play, which through their spontaneity allow the individual to develop traits and skills desired by the contemporary society. The final part offers guidelines for educational practice, where the author indicates opportunities to create situations when children can play and adults can accompany them in the play, create the play together with children, etc. She underlines the role of adults in organising opportunities for play free from hurry and time pressure.